The Price-Concentration Relationship in Banking: A Reply - Berger, Allen N.; Hannan, Timothy H. (The Review of Economics and Statistics, 1992)
Berger, Allen N., and Timothy H. Hannon, The Price-Concentration Relationship in Banking, this REVIEW 71 (May 1989), 291-299. Demsetz, Harold, Industry Structure, Rivalry, and Public Policy, Journal of Law and Economics 16 (Apr. 1973), 1-9. Jackson, William E. III, Market Structure and Price Adjustments: Evidence from the Banking Industry, unpublished Ph.D. dissertation, University of Chicago, June 1989. Peltzman, Samuel, The Gains and Losses from Industrial Concentration, Journal of Law and Economics 20 (Oct. 1977), 229-263. Salinger, Michael, The Concentration-Margins Relationship Reconsidered, in Brookings Papers on Economic Activity: Microeconomics, Martin N. Bailey and Clifford Winston, (eds.), Brookings (Washington, D.C.: Brookings Institution, 1990). 5 No formal statistical tests of the differences in the estimated coefficients of CONC across subsamples were conducted. This analysis was concerned more with the sign and significance level of each subsample estimated CONC coefficient.